A binuclear copper(II) complex with diphenoxido-bridges: synthesis, characterisation, crystal structure and predicting the magnetic coupling constant. (1st February 2016) - Mashhun, Asmar; Zarei, Seyed Amir; Piltan, Mohammad; Chevreux, Sylviane; Guillon, Emmanuel
Reaction of copper(II) acetate with 1, 1'-[(2, 2-dimethylpropane-1, 3-diyl)bis(nitrilomethylidyne)]-di-2-naphthol (H2L) gave the diphenoxido-bridged binuclear copper(II) complex [Cu2L2]. Its crystal structure shows a slightly distorted square pyramidal geometry around both of the copper(II) ions. In the symmetric Cu2O2 core, each of the phenoxido bridges occupies an equatorial position around one of the copper(II) centres. A broken symmetry (BS) computation based on density functional theory (DFT) evaluated the magnetic interaction in the complex using the (U)B3LYP level of theory in association with the basis sets LANL2DZ for the copper atoms and 6-31G** for the other atoms. The calculations showed ferromagnetic interaction between the two magnetic copper(II) centres with a magnetic coupling constant (J) of 1.16 cm–1.